2016
DOI: 10.1111/geb.12509
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis of traits predicting species sensitivity to habitat fragmentation

Abstract: Aim Elucidating patterns in species responses to habitat fragmentation is an important focus of ecology and conservation, but studies are often geographically restricted, taxonomically narrow or use indirect measures of species vulnerability. We investigated predictors of species presence after fragmentation using data from studies around the world that included all four terrestrial vertebrate classes, thus allowing direct inter-taxonomic comparison.Location World-wide.Methods We used generalized linear mixed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
174
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(183 citation statements)
references
References 57 publications
6
174
2
1
Order By: Relevance
“…This is likely due to the fact that birds can migrate among patches, and mobility is a key factor determining species responses to habitat fragmentation (Fuentes‐Montemayor, Watts, Macgregor, Lopez‐Gallego, & Park, ). However, the generalization may not hold for territorial birds or those that do not move between patches and are sensitive to habitat fragmentation (Keinath et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the fact that birds can migrate among patches, and mobility is a key factor determining species responses to habitat fragmentation (Fuentes‐Montemayor, Watts, Macgregor, Lopez‐Gallego, & Park, ). However, the generalization may not hold for territorial birds or those that do not move between patches and are sensitive to habitat fragmentation (Keinath et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These traits are often associated with high vulnerability to habitat conversion (Tscharntke et al 2002, Le Viol et al 2012, Keinath et al 2017, while broad habitat range, exogenous origin and generalist diet favor tolerance to anthropogenic disturbance (Rayner et al 2015). In line with these general patterns, a meta-analysis pointed reptiles' habitat specialization to explain their high sensitivity to landscape fragmentation (Keinath et al 2017). This result was further supported by a regional study in eastern North America, which showed that high human imprint on land use threaten snakes with carnivorous diets, low reproductive rates, fossorial and aquatic habitats (Todd et al 2017).…”
Section: Opportunistic Records Reveal Mediterranean Reptiles' Scale-dmentioning
confidence: 92%
“…Reptiles have recently undergone declines at regional (Driscoll 2004) and global scales (Gibbons et al 2000, Keinath et al 2017, partly explained by ecological trait suites associated with vulnerability to anthropogenic disturbance of resources and habitats (Cardillo et al 2005, Trimble andvan Aarde 2014). As ectothermic predators, most reptile species combine small home ranges, high habitat and dietary specialization, low dispersal and sensitivity to microclimates (Huey 1982).…”
Section: Opportunistic Records Reveal Mediterranean Reptiles' Scale-dmentioning
confidence: 99%
“…It seems that despite the change in environmental conditions and growth of total available N (g/m 2 ) in soils (Göransson et al, 2016), δ 15 N values in aurochs did not increase. Habitat specialists are more sensitive to environmental changes and vulnerable to extinction (Keinath et al, 2017). Thus, the limits set by ecological conditions of forest habitats (i.e.…”
Section: Stable Isotopic Compositions Show a Significant Shift Of Formentioning
confidence: 99%
“…Large mammals are particularly vulnerable to environmental changes and habitat fragmentations and exposed to risk of extirpation or extinction due to their body size, lower densities, larger spatial requirements and disproportional exploitation by humans, particularly more specialized species that have a lower capacity for adaptation (Cardillo et al, 2005;Keinath et al, 2017). Opening of forest habitats would have created more optimal foraging conditions for grazers, less for browsers, but might have exposed them to increased human pressure and had similar effects (reduced fitness, population fragmentation and local extinction).…”
Section: Introductionmentioning
confidence: 99%